2020
DOI: 10.21203/rs.3.rs-25728/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Far-UVC light efficiently and safely inactivates airborne human coronaviruses

Abstract: A direct approach to limit airborne transmission of pathogens is to inactivate them within a short time of their production. Germicidal ultraviolet light (UV), typically at 254 nm, is effective in this context, but it is a health hazard to the skin and eyes. By contrast, far-UVC light (207-222 nm) efficiently kills pathogens without harm to exposed human cells or tissues. We previously demonstrated that 222-nm UV light efficiently kills airborne influenza virus (H1N1); here we extend the far-UVC studies to exp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1
19

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 26 publications
0
25
1
19
Order By: Relevance
“…Use in public locations at the current regulatory exposure limit (∼3 mJ/cm 2 /hour) would result in approximately 90% viral inactivation in 8 minutes and 99.9% inactivation in ∼25 minutes. 82 Therefore, ultraviolet light can be used to disinfect surfaces and equipment after the manual chemical disinfection process is completed to shield against errors in the manual disinfection process.…”
Section: Introductionmentioning
confidence: 99%
“…Use in public locations at the current regulatory exposure limit (∼3 mJ/cm 2 /hour) would result in approximately 90% viral inactivation in 8 minutes and 99.9% inactivation in ∼25 minutes. 82 Therefore, ultraviolet light can be used to disinfect surfaces and equipment after the manual chemical disinfection process is completed to shield against errors in the manual disinfection process.…”
Section: Introductionmentioning
confidence: 99%
“…Looking at the general similarities between the currently spreading SARS-CoV-2 and SARS-CoV and MERS-CoV, it can be presumed that UVGI is also effective in deactivating SARS-CoV-2. The problem of deactivating the pathogen by UVC radiation can be also found in many recent publications [ 3 , 4 , 5 , 6 ]. The primary purpose of our research is to develop the device and determine its effectiveness.…”
Section: Introductionmentioning
confidence: 93%
“…However, exposure to these lamps has been associated with health risks, which mainly involve damage to the eyes and skin [ 81 , 82 ]. Nevertheless, recent evidences suggested that UV-C at 222 nm exhibited germicidal activity [ 83 , 84 , 85 ], but inflicted no damage on the eyes and skin of mice [ 86 , 87 , 88 ]. These data are still preliminary and further research is needed to ascertain the safety of UV light at 222 nm, especially its potential long-term effects on human health.…”
Section: Viral Properties Of Ultraviolet Lightmentioning
confidence: 99%